Closed circuit rebreathing to achieve inert gas wash-in for multiple breath wash-out - Horsley, Alex R.; O'Neill, Katherine; Downey, Damian G.; Elborn, J. Stuart; Bell, Nicholas J.; Smith, Jaclyn; Owers-Bradley, John (European Respiratory Society, 2016)
Multiple breath wash-out (MBW) testing requires prior wash-in of inert tracer gas. Wash-in efficiency can be enhanced by a rebreathing tracer in a closed circuit. Previous attempts to deploy this did not account for the impact of CO2 accumulation on patients and were unsuccessful. We hypothesised that an effective rebreathe wash-in could be delivered and it would not alter wash-out parameters.